Decentralization reforms and their relations to local democracy and efficiency: CEE lessons - Juraj Nemec (Central European Public Administration Review)
The paper discusses the implementation of decentralization in Central and Eastern Europe Countries after the signature and ratification of the European Charter of Local Self-Government. Decentralization as one of the reform approaches has several positive impacts on governance, but might have negative consequences, too. There are issues concerning allocation of financial resources, optimal territorial structure, weak local democracy. Local government units, especially the smaller ones, are not cost effective neither in administration nor in managing quality and expenditure of public services. For the reforms to realise the necessary democracy and efficiency, the author proposes to respect some principles of implementing decentralization.